METHODOLOGICAL PROPERTIES OF INTER-SUBJECT RELATIONS OF PHYSICS WITH BIOLOGY IN MEDICAL UNIVERSITIES (Ta'limning zamonaviy transformatsiyasi, 2024)
The didactic possibilities of teaching physics in connection with biology by high school students of secondary schools on the elementary fundamentals of biophysical science are considered.